2022
DOI: 10.1177/10870547221085493
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Sluggish Cognitive Tempo, Internalizing Symptoms, and Academic Performance in Children With Reading Disorder: A Longitudinal Cohort Study

Abstract: Objective: To investigate whether sluggish cognitive tempo (SCT) was associated with anxiety, depression, and academic performance (AP) in children with reading disorder (RD), and whether ADHD-Inattention (ADHD-IN) moderated these relationships. Method: Parents and teachers of children with RD ( N = 147, ages 6–18) completed evaluations of SCT, ADHD, anxiety, depression, and AP, every 3 months for 18 months. Baseline and longitudinal associations between SCT and outcomes, and effect moderation of ADHD-IN, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…As previously known, maladjustment is strongly correlated with anxiety, which is often manifested as worries and fears of external uncontrollable factors. Existing studies have also revealed that SCT was more associated with anxiety and depression symptoms occurrences than ADHD 40 . Corresponding to Sevincok et al who proposed that while the externalization symptoms were related to ADHD 41 , SCT was more associated with internalization symptoms more prominently, findings in our research provide further empirical support on the distinctions between ADHD and SCT.…”
Section: Discussionmentioning
confidence: 99%
“…As previously known, maladjustment is strongly correlated with anxiety, which is often manifested as worries and fears of external uncontrollable factors. Existing studies have also revealed that SCT was more associated with anxiety and depression symptoms occurrences than ADHD 40 . Corresponding to Sevincok et al who proposed that while the externalization symptoms were related to ADHD 41 , SCT was more associated with internalization symptoms more prominently, findings in our research provide further empirical support on the distinctions between ADHD and SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the above stance, the research findings among individuals with LDs have shown that the difficulties can generate resilience-promoting experiences (McNulty, 2003 ; Nalavany et al, 2011 ). Accordingly, the view that resilience could alleviate mental health problems among individuals with LDs (Haft et al, 2016 ) is supported by the findings indicating that increased grit and resilience have been associated with less anxiety and depression among children with RD (Hossain et al, 2022 ) and that better resilience explains general, self-, and social satisfaction (Stack-Cutler et al, 2015 ). Thus, it can be hypothesized that after a setback, a low level of resilience may promote an anticipation of failure, which, in turn, can reduce resilience, creating a vicious circle leading to poorer mental health.…”
Section: Rd MD Rd + Md and Mental Healthmentioning
confidence: 97%
“…Cognitive inattention is connected to student's inability to pay attention to their education, which results in a decreased capacity for learning in their coursework. The term "cognitive inattention" refers to a general decline in a person's mental capabilities, including reasoning, problem-solving, planning, abstract thought, understanding complicated ideas, and learning from experience (Hossain et al, 2022). The vast majority of studies agree that cognitive inattention is a factor that contributes to performance anxiety as well as academic failure.…”
Section: Cognitive Inattention and Performance Anxietymentioning
confidence: 99%
“…According to the findings of several studies, students who are incapacitated by their anxiety around their potential for failure exhibit symptoms of sadness or panic. Fear of failing a test has been investigated in order to get a better understanding of the learning behaviours of students, and it was shown that this fear is related to the evaluations of potential risks to the individual's capacity to achieve their objectives (Hossain et al, 2022). Based on the above literature, we hypothesize the following: Hossain et al (2022).…”
Section: Lack Of Preparation Performance Anxiety and Academic Failurementioning
confidence: 99%
See 1 more Smart Citation